UNIVERSALITY OF THE RULE OF LAW;UNIVERSALITY OF THE RULE OF LAW (AFRICAN SUN MEDIA, 2021)
The book is the result of a recent but intensive cooperation between the faculties of law of the universities of Ljubljana and Johannesburg. As is often the case in life, the starting point of this project was a friendship. A friendship between two law professors who, at the same point in time, became deans of their respective law schools - Prof Letlhokwa Mpedi (now Deputy Vice-Chancellor: Academic (UJ)) in Johannesburg and Prof Grega Strban in Ljubljana.</bod.